Psychological Factors for Computer Game Addiction of Young Adolescents - Viktorovna Grishina, Anna; Nikolaevna Volkova, Elena (International Journal of Engineering and Technology, 2018)
consider the psychological features regarding the development of younger adolescents, the violation of which may be the cause of computer game addiction at a given age stage of development. The issue of the influence of computer game addiction on the mental and personal development of a younger adolescent has not been studied enough. An analysis of psychological studies has shown that the psychological factors, conditions and mechanisms that determine the characteristics of computer game addiction in early adolescence are not adequately worked out. In this study, a theoretical analysis of personal prerequisites for the development of computer game addiction in younger adolescents was conducted, which allowed determining that computer game addiction arose from a combination of two groups of factors: personal and socio-psychological. The personal factors of computer game addiction in younger adolescents were revealed: inadequate, often overestimated self-esteem, increased desire for risk and search for acute sensations, weak volitional potential, unbalanced development of a child’s agency. The socio-psychological factors of computer game addiction in eatly adolescence were revealed, which were a combination of the features of child-parent relations and the characteristics of the child’s interaction with peers. Â Â